A Review of Mixed Strain Clostridium difficile Colonization and Infection - Dayananda, Pete; Wilcox, Mark H. (Frontiers in Microbiology, 2019)
Given that Clostridium difficile is not part of the normal human microbiota, if multiple strains are to accumulate in the colon implies successive exposure events and/or persistent colonisation must occur. Evidence of C. difficile infection (CDI) with more than one strain was first described in 1983. Despite the availability of increasingly discriminatory bacterial fingerprinting methods, the described rate of dual strain recovery in patients with CDI has remained stable at ~5-10%. More data are needed to determine when dual strain infection may be harmful. Notably, one strain may block the establishment of and infection by another. In humans, patients colonised by non-toxigenic C. difficile strain are at a lower risk of developing CDI. Further studies to elucidate the interaction between co-infecting or colonising and infecting C. difficile strains may help identify potential exploitable mechanisms to prevent CDI.